Social pedagogy, music making and adopted children (International Journal of Social Pedagogy, 2020)
Social pedagogy has become a common feature of CPD training for staff working with looked after children and adopted children. Social workers, foster carers and adoptive parents use the characteristic features of social pedagogical practice to develop meaningful relationships with a young person in care. Creative elements such as music have been noted to be useful activities in which both parties (children and support worker) can share a common interest and partake within a joint activity. This article sets out to examine the way in which a community music project working with adopted children and their adoptive parents uses social pedagogy and the impact that this may have on the participants. A case study strategy is used to examine the Loud and Clear adoption family learning project at Sage Gateshead, through which a multi-methodological approach was used, including interviews and participatory action research to gather participants’ and facilitators’ narratives of the impacts the sessions and approaches were having. Furthermore, participatory observations were also undertaken to see at first hand the social pedagogical approaches that the facilitators were using within sessions. Findings from the study indicated that having the opportunity to participate in a joint musical activity was key to helping children and adoptive parents develop their attachments to one another. Similarly, through facilitators providing opportunities for the group to socialise, adoptive parents were able to develop a support network that they felt would have been lacking within their lives. Both of these findings indicate the impact of adopting the common third approach to music making.